Implementasi Model Praktek Keperawatan Profesional (MPKP) terhadap Kepuasan Pelanggan dan Kepuasan Kerja Perawat - Sucy Hasfya; Chrismis Novalinda Ginting; Ali Napiah Nasution (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the implementation of the Professional Nursing Practice Model (MPKP) on customer satisfaction and job satisfaction of nurses at RSU Royal Prima Medan. The research method used in this study is a quantitative method with a cross-sectional approach. The results showed that if the implementation of MPKP at RSU Royal Prima Medan went well, then 186 nurses felt fasting with a percentage of 88.6%. No nurses were dissatisfied, and if MPKP implementation at RSU Royal Prima Medan went wrong well, 15 nurses were satisfied with a rate of 7.1%. Nine nurses were disappointed, with a percentage of 4.3%. The results of the chi-square test obtained a p-value of 0.000 <0.05. In conclusion, there is a relationship between the implementation of the Professional Nursing Practice Model (MPKP) on the job satisfaction of nurses at RSU Royal Prima Medan. Keywords: Nurse Job Satisfaction, Patient Satisfaction, MPKP